(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In the Ríos, Ecuador, small family systems that use trees and shrubs in feed animals are recognized as a source of livestock production, so it would be practical to classify them. White Objective typifies livestock farms in the province's north, emphasizing trees and shrubs in animal feed. Random sampling was applied. Out of a total of 320 farms, 98 were chosen at random (case under study). The experiment was carried out in different places that comprise the cantons: Buena Fé, Valencia, Quevedo y Quinsaloma. Menans of multivariate analysis classified cases. Factor analysis (FA) and cluster analysis (CA) were used. For the FA several extraction methods were explored, finally selecting the method of categorical principal components. The study showed that the variables originated in order of priority three components, which explained more than 73% of the total variance. It was observed that 18 variables of the total were represented with factor loadings higher than 0,75 in some components. The hierarchical conglomerate defined the grouping and classification of the farms. At 30% of the Euclidean distance, three groups were obtained, which define the organization of the herd and the productive purpose. The groups were basically differentiated by the size of the farms, the use they give to the trees, the number of hectares dedicated to pastures, and the species of trees they have in the pastures.